Detection of Escherichia coli and Enterococcus spp. in dogs with polymicrobial urinary tract infections: A 5‐year retrospective study. (27th May 2022) - Walker, Grayson K.; Yustyniuk, Valeriia; Shamoun, John; Jacob, Megan E.; Correa, Maria; Vaden, Shelly L.; Borst, Luke B.
Abstract: Background: Urinary tract infections (UTI) caused by Escherichia coli and Enterococcus spp., which are frequently coisolated in polymicrobial UTI, cause morbidity among dogs and warrant antimicrobial therapy. Objectives: To evaluate clinical features of dogs with polymicrobial E. coli and Enterococcal UTI. Animals: Forty‐four client‐owned dogs with polymicrobial bacteriuria and groups of 100 client‐owned dogs with E. coli and Enterococcal monomicrobial bacteriuria. Methods: Retrospective cohort study of medical records of dogs at a university teaching hospital from 2014 to 2019. Prevalence of recurrent UTI and isolate antimicrobial resistance were determined. Clinical outcomes of dogs with recurrent UTI from groups including cost and hospital visits were compared. Results: Recurrent UTI was more prevalent ( P  = .05) in dogs with polymicrobial bacteriuria (57%, 95% confidence interval [95% CI]: 42%‐70%) compared to the Enterococcal monomicrobial group (40%, 95% CI: 31%‐50%). Escherichia coli from polymicrobial bacteriuria were more frequently resistant to doxycycline ( P  < .01, 43%, 95% CI: 29%‐58%) and gentamicin ( P  = .03, 17%, 95% CI: 9%‐31%) compared to E. coli from monomicrobial bacteriuria (17% and 5%, 95% CI: 11%‐26% and 2%‐11% for doxycycline and gentamicin, respectively). Dogs with recurrent UTI from the polymicrobial UTI group had significantly ( P  = .05) more hospital visits (mean = 6 visits, 95% CI: 1.7‐9.8) compared to recurrent monomicrobial UTI dogs (mean = 4 and 3 visits, 95% CI: 1.0 to 4.4 and −0.7 to 7.7 for E. coli and Enterococcal monomicrobial UTI, respectively). Conclusions and Clinical Importance: Escherichia coli and Enterococcus spp. polymicrobial UTI had more frequent adverse clinical outcomes for dogs.